Application of CORS in Landslide Monitoring. Issue 4 (October 2021) - Zhao, W Y; Zhang, M Z; Ma, J; Han, B; Ye, S Q; Huang, Z
Abstract: Global Navigation Satellite System (GNSS) can provide continuous and high-precision absolute displacement information and therefore has been an important technical means of landslide surface displacement monitoring. When GNSS is used for landslide monitoring, a reference station is usually set for a monitoring landslide (referred to as "one reference station for one landslide"). Through the method of short baseline relative positioning, high-precision monitoring is realized by eliminating the atmospheric propagation error with strong spatial correlation. However, this application mode has problems such as high monitoring cost, low data reuse of reference station, and heavy dependence on the single reference station for the calculation results of monitoring stations, which limit the large-scale promotion and application of GNSS in landslide monitoring. Aiming at the above problems, this study took Liujiafen Landslide in Maoxian County, Sichuan Province as a case to study the application of Continuously Operating Reference Stations (CORS) and Virtual Reference Station (VRS) issued by Natural Resource system in landslide monitoring to optimize the existing application mode of "one reference station for one landslide". In this study, the evaluation of the quality of VRS data, the calculation accuracy of static base line, and the comparative analysis of the calculation results between virtual and physical reference stations were carried out to demonstrate the applicability of CORS in landslide monitoring. According to the results: (1) The data quality of the selected virtual reference station was good; (2) The calculation accuracy of the baseline composed of virtual reference station and monitoring station was basically equal to that of the baseline composed of physical reference station and monitoring station. In view of the regional differences in the construction density and quality of CORS reference stations, and the relationship between atmospheric propagation correction model and topographic relief, it is suggested that the application should be decided after comprehensive evaluation based on the actual distribution of reference stations and specific environmental conditions.